Calculated Thermal Performance of Solar Collectors Based on Measured Weather Data from 2001-2010. (May 2015) - Dragsted, Janne; Furbo, Simon; Andersen, Elsa; Perers, Bengt; Nielsen, Kristian P.
Abstract: This paper presents an investigation of the differences in modeled thermal performance of solar collectors when meteorological reference years are used as input and when mulit-year weather data are used as input. The investigation has shown that using the Danish reference year based on the period 1975-1990 will result in deviations of up to 39% compared with thermal performance calculated with multi-yearmeasured weather data. For the newer local reference years based on the period 2001-2010 the maximum deviation becomes 25%. The investigation further showed an increase in utilization with an increase in global radiation. This means that besides increasing the thermal performance with increasing the solar radiation, the utilization of the solar radiation also becomes better.